Natural Orifice Endosonographic Colposuspension With Rectopexy for Combined Pelvic Organ Prolapse: A Feasibility Study. Issue 3 (March 2022) - Chandra, Abhijit; Rajan, Pritheesh; Gupta, Vivek; Ahmad, Arshad; Parihar, Anit; Yadav, Gourav; Singh, Uma; Rajashekhara, Mahesh; Patankar, Sanjiv K.; Patel, Ravi
Abstract : BACKGROUND: We describe a natural orifice technique for simultaneous endoluminal lateral suspension of apical vaginal wall and rectal prolapse fixation with ultrasound and fluoroscopic assistance. IMPACT OF INNOVATION: The technique is minimally invasive, can be performed under regional anaesthesia, and avoids laparotomy or use of a mesh in addition to preserving the uterus. TECHNOLOGY MATERIALS AND METHODS: This technique involves suprapubic transvaginal ventral suture colposuspension, fixation of the anterior rectal wall to the undersurface of the anterior abdominal wall and tack fixation of the posterior rectal wall to the underlying sacral promontory through a submucosal tunnel performed endoscopically with fluoroscopic and ultrasound assistance. PRELIMINARY RESULTS: Seven patients with a mean age of 63 years were followed between 3 to 11 months. CONCLUSIONS: This is a novel minimally invasive transluminal procedure that repairs concomitant rectal and vaginal prolapse in the same sitting. FUTURE DIRECTIONS: Improvement in the instrument design and incorporation of endoluminal robotic systems will enhance the technical ease. The study needs validation in larger series of patients with longer follow-up.